Update on Hepatitis C Virus (HCV) Vaccine Candidates in Clinical Trials: A Systematic Literature Review - Ratnoglik, Suratno Lulut; Harumdini, Matahari (CV. Publikasi Indonesia, 2024)
Introduction: Hepatitis C virus (HCV) infection remains a significant global health challenge, affecting over 71 million people worldwide and leading to severe liver diseases such as cirrhosis and hepatocellular carcinoma (HCC). Despite the availability of highly effective direct-acting antiviral (DAA) therapies achieving sustained virologic response (SVR) rates exceeding 90%, high costs and limited accessibility impede global eradication efforts. Additionally, DAAs do not confer immunity against reinfection, highlighting the need for a prophylactic vaccine. Methods: This systematic literature review follows the PRISMA guidelines. A comprehensive search was conducted in PubMed, Scopus, and Web of Science for articles published between January 2010 and March 2024, focusing on HCV vaccine candidates in clinical trials. Data on study characteristics, participant demographics, vaccine characteristics, vaccine platforms and key outcomes were extracted. Results: Nine studies met the eligibility criteria, covering various phases of clinical trials (Phase I, II, and II/III). Key findings included: Vaccine platforms: The studies primarily utilized three types of vaccine platforms: Viral Vector-Based Vaccines, Peptide-Based Vaccines and Recombinant Protein Vaccines Immunogenicity: Vaccines targeting non-structural proteins (NS3, NS4, NS5) induced robust T-cell responses. Chimpanzee adenovirus (ChAd) and Modified Vaccinia Ankara (MVA) vector-based vaccines showed high polyfunctional CD8+ and CD4+ T-cell levels. Safety: Most adverse events were mild to moderate, including flu-like symptoms and injection site reactions. Severe adverse events were noted with TG4040 when combined with PEG-IFNα and RBV. Efficacy: Significant reductions in viral load and improvements in liver function were reported. Personalized peptide vaccines demonstrated enhanced immune responses and improved overall survival in HCV-positive advanced HCC patients. Conclusion: HCV vaccine development has made significant strides, with several candidates demonstrating strong immunogenicity, acceptable safety, and promising efficacy in clinical trials. Continued research is essential to address challenges such as viral genetic variability, durability of immune responses, and global accessibility.